2011
DOI: 10.4103/0971-6866.82190
|View full text |Cite
|
Sign up to set email alerts
|

MCT oil-based diet reverses hypertrophic cardiomyopathy in a patient with very long chain acyl-coA dehydrogenase deficiency

Abstract: Very long chain acyl-CoA dehydrogenase (VLCAD) deficiency is one of the genetic defects of mitochondrial fatty acid beta-oxidation presenting in early infancy or childhood. If undiagnosed and untreated, VLCAD deficiency may be fatal, secondary to cardiac involvement. We assessed the effect of replacing part of the fat in the diet of a 2 ½-month-old male infant, who was diagnosed with VLCAD deficiency,with medium-chain triglyceride (MCT) oil and essential fats. The patient presented with vomiting, dehydration, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…VLCAD À/À in humans by reversing cardiomyopathy [18,19], and in mice by preventing the development of the muscular phenotype when applied as a bolus immediately prior to exercise [24]. As we previously observed that long-term application of MCTs induces a severe phenotype resembling metabolic syndrome [22], we hypothesize that most of the supplemented MCTs are elongated and accumulate as LCFAs.…”
Section: Wtmentioning
confidence: 65%
See 1 more Smart Citation
“…VLCAD À/À in humans by reversing cardiomyopathy [18,19], and in mice by preventing the development of the muscular phenotype when applied as a bolus immediately prior to exercise [24]. As we previously observed that long-term application of MCTs induces a severe phenotype resembling metabolic syndrome [22], we hypothesize that most of the supplemented MCTs are elongated and accumulate as LCFAs.…”
Section: Wtmentioning
confidence: 65%
“…All animal studies were performed with the approval of the University's Institutional Animal Care and Use Committee, and in accordance with the Committee's guidelines. Approval was given by the Regierungspr€ asidium Freiburg, Abteilung Landwirtschaft, L€ andlicher Raum, Veterin€ arund Lebensmittelwesen (File number: .81/G- [14][15][16][17][18][19][20].…”
Section: Methodsmentioning
confidence: 99%
“…One possibility for this high apparent carrier rate is that the second pathogenic allele was missed by Sanger sequence analysis. We could find at least one example in the literature of a patient with a large deletion in ACADVL who was missed by Sanger sequence analysis [24]. Alternatively, variants affecting deep intronic or promoter sequence may also be missed by the Sanger analysis we provide.…”
Section: Discussionmentioning
confidence: 99%
“…37 MCT supplementation has been associated with a reversal of cardiomyopathy in case reports of patients with CACT and VLCAD deficiency. 28,38,39 However, reports have noted that even highly compliant VLCAD patients still had significant muscle weakness, muscle pain, or myoglobinuria. 17 Although secondary carnitine deficiency is common in the LCFAO disorders, carnitine supplementation is controversial.…”
Section: Current Therapiesmentioning
confidence: 99%